Use of single-gene reassortant viruses to study the role of avian influenza A virus genes in attenuation of wild-type human influenza A virus for squirrel monkeys and adult human volunteers. - Clements, M L (1992)
The transfer of six internal RNA segments from the avian influenza A/Mallard/New York/6750/78 (H2N2) virus reproducibly attenuates human influenza A viruses for squirrel monkeys and adult humans. To identify the avian influenza A virus genes that specify the attenuation and host range restriction of avian-human (ah) influenza A reassortant viruses (referred to as ah reassortants), we isolated six single-gene reassortant viruses (SGRs), each having a single internal RNA segment of the influenza A/Mallard/New York/6750/78 virus and seven RNA segments from the human influenza A/Los Angeles/2/87 (H3N2) wild-type virus. To assess the level of attenuation, we compared each SGR with the A/Los Angeles/2/87 wild-type virus and a 6-2 gene ah reassortant (having six internal RNA segments from the avian influenza A virus parent and two genes encoding the hemagglutinin and neuraminidase glycoproteins from the wild-type human influenza A virus) for the ability to replicate in seronegative squirrel monkeys and adult human volunteers. In monkeys and humans, replication of the 6-2 gene ah reassortant was highly restricted. In humans, the NS, M, PB2, and PB1 SGRs each replicated significantly less efficiently (P less than 0.05) than the wild-type human influenza A virus parent, suggesting that each of these genes contributes to the attenuation phenotype. In monkeys, only the NP, PB2, and possibly the M genes contributed to the attenuation phenotype. These discordant observations, particularly with regard to the NP SGR, indicate that not all genetic determinants of attenuation of influenza A viruses for humans can be identified during studies of SGRs conducted with monkeys. The PB2 and M SGRs that were attenuated in humans each exhibited a new phenotype that was not observed for either parental virus. Thus, it was not possible to determine whether avian influenza virus PB2 or M gene itself or a specific constellation of avian and human influenza A virus specified restriction of virus replication in humans.